The Influence of Customer Experience, Brand Image, and Price Perception on Customer Loyalty through Customer Satisfaction of Gojek Users at Universitas Sumatera Utara - Endang Lestari; Lubis, Arlina Nurbaity; Sembiring, Beby Karina Faw zeea (PT FORMOSA CENDEKIA GLOBAL, 2025)
The presence of increasingly sophisticated digital technology has brought extraordinary changes and progress to human life. One digital technology that is often used is online applications. In this modern era, transportation has become an important support for daily activities, especially in urban areas. Based on a survey conducted by Inrix 2023, it was stated that the city of Medan has the highest level of congestion in large cities in Indonesia. Companies providing online transportation services are expected to increase customer loyalty and satisfaction. This research aims to determine and analyze the influence of customer experience, brand image, price perception on customer loyalty through Gojek customer satisfaction at the University of North Sumatra.